Bridging advertising practitioner theories and academic theories on how to communicate effectively with men and women. Issue 3 (10th June 2019) - Windels, Kasey
Abstract : Purpose: The purpose of this paper is to understand advertising practitioners' theories on how to communicate effectively with men and women via advertising. Further, comparisons are made between practitioners' theories and academic research. Design/methodology/approach: Qualitative interviews were conducted with 39 US advertising practitioners. Findings: Many professionals believed women preferred other-oriented messages, while men preferred self-oriented messages. They believed women were comprehensive processors, while men were less engaged with advertising messages. They believe men preferred slapstick humor and factual messages, while women preferred emotional appeals. Research limitations/implications: Comparisons between practitioners' perspectives and the academic research reveal that practitioners' theories often correspond to academic theories and empirical data. Relationships with the selectivity hypothesis are explored in depth. Suggestions are made to extend existing theory to test practitioners' theories. Practical implications: This study helps to bridge the academician-practitioner gap, which helps academics understand practitioners, communicate with them and develop shared knowledge. Originality/value: This study fills a research gap in understanding practitioners' theories of how to communicate with men and women. A key contribution of the research is a comparison of practitioner theories with academic research to note points of agreement and disagreement, bridge the gap and offer suggestions for future research.